Geology of U.S. parklands - Kiver, Eugene P. (J. Wiley, 1999)
Requiring no prior familiarity with the geological sciences, this region-by-region exploration of the U.S. parklands teaches the principles of physical and historical geology by example. It begins with a general introduction to all important concepts, terms, and principles. In the chapters that follow, the authors take you on a tour through the geological regions of the United States. Beginning with Hawaii and the Pacific borderlands and moving progressively eastward to the Appalachian Mountains and the coastal plains of the East Coast, they provide you with a geologist's-eye view of the landforms, mountains, and bodies of water encountered in over 70 national parks and monuments, and tell the fascinating story of their evolution.